Integrating demand-responsive transportation. Bridging the gap between public transit and individual mobility in a Mobility-as-a-Service ecosystem. - Foljanty, Lukas; Wilhelms, Mark-Philipp (Trialog Publishers, 2020)
New mobility services are expanding quickly, putting pressure on public transit. Cities are challenged to embrace mobility innovations while meeting overarching public mobility objectives. In the advent of autonomous driving, taking an active role becomes ever more important for cities. Digitalization enables cities to become mobility orchestrators by building an integrated urban mobility ecosystem and flexibilizing traditional public transit via the means of demand-responsive transit. We discuss critical ingredients to a successful implementation of a city-operated on-demand MaaS landscape.
Keywords: Öffentlicher Verkehr; Individualverkehr; Innovation; Digitalisierung; Nachfrageorientierung; Verkehrsangebot; Verkehrssystem; Integration; Stadtverkehr; Fallbeispiel; Mobility-as-a-Service